THE IMPLEMENTATION OF SONGS IN TEACHING ENGLISH TO ELEMENTARY SCHOOL - Kurnia Budiyanti; Nefiyandra, Tasya; Dinda Alfiah Nahdah Simanjuntak; Ira Riswana; Nurhamidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to investigate the implementation of songs in teaching English to elementary school students at SD 136 Pekanbaru. This study employed a qualitative descriptive design. The instruments used were questionnaires, interviews, and documentation. The questionnaire was distributed to 28 students to identify their responses toward the use of songs in learning English, while the interview was conducted with the English teacher to obtain information about the implementation of songs in the classroom. The findings showed that songs received positive responses from students in learning English. Songs increased students’ motivation, participation, vocabulary mastery, and pronunciation. The teacher also stated that songs created an enjoyable classroom atmosphere and encouraged students to participate actively during the lesson. However, several challenges remained, particularly limited classroom facilities such as speakers and LCD projectors. Overall, songs were considered an effective and